The sulfur cycle below the sulfate-methane transition of marine sediments. (15th October 2018) - Pellerin, André; Antler, Gilad; Røy, Hans; Findlay, Alyssa; Beulig, Felix; Scholze, Caroline; Turchyn, Alexandra V.; Jørgensen, Bo Barker
Abstract: The study of sulfate reduction below the sulfate-methane transition (SMT) in marine sediments requires strict precautions to avoid sulfate contamination from seawater sulfate or from sulfide oxidation during handling. We experimented with different methods of sampling porewater sulfate and found that modifications to our sampling procedure reduced the measured sulfate concentrations from hundreds of micromolar to ten micromolar or less. We here recommend some key modifications to porewater sampling to avoid contamination or oxidation artifacts, for example when measuring very low sulfate concentrations below the SMT of marine sediments. At three sites in Aarhus Bay, the sulfate concentrations below the SMT remained around ten micromolar. The calculated free energy change, ΔGr, available for sulfate reduction by such low concentrations is between −17.9 and −11.9 kJ mol −1 sulfate. This is near or below the energy yields that have previously been calculated for microbial sulfate reduction in marine sediments. The three sites are characterized by measurable and very different sulfate reduction rates depending on the depth and sediment age of the SMT. Our data show that sulfate is being consumed below the SMT in spite of the low sulfate concentrations. As sulfate is not drawn down to even lower concentrations, it must be continually regenerated below the SMT, most likely by Fe(III)-driven sulfide oxidation concurrent with the sulfate reduction. We conclude that the low sub-SMT sulfate concentrations are in steady state between reduction and production and are thermodynamically controlled by the minimum ΔGr requirements by sulfate reducing bacteria while sulfate reduction rates are controlled by the rate of sulfide oxidation. This study deals with the general sampling of uncontaminated pore water and hints to a systemic problem with low levels of contamination in porewater induced by coring and pore water extraction. Below the SMT, this contamination could be detected but above the SMT it goes unnoticed. Low levels of contamination as observed in this study may affect other low concentration or redox-sensitive elements in pore water.